The Unique Nature of Cilember Curug Megamendung as a Main Destination - Mularsari, Ardi; Nugraha, Rizki Nurul (Westscience Press, 2023)
This research discusses the uniqueness of the tourist destination at Curug Cilember as a mainstay destination. Cilember Waterfall is located in Megamendung, Cilember Village, Cisarua District, Bogor Regency. Officially operating since 2000, Curug Cilember Megamendung has an attraction in the form of seven beautiful and natural waterfalls, with the height of the waterfall, the width of the water flow, the beauty of the surrounding scenery, various recreational activities that can be done with the family, ease of transportation and travel routes. to be accessed by private vehicles and public transportation, so it can be indicated as a mainstay destination. The research methods used include direct observation, interviews with local people, and document analysis. A qualitative descriptive approach was used to fully understand the natural beauty of Curug Cilember. The aim of this research is to identify the uniqueness and other potential of Curug Cilember Megamendung including biodiversity, surrounding environment and attractiveness. The research results show that all the beauty of Curug Cilember is able to make it a mainstay destination and can be perfected again with a tour package and overcoming challenges that may occur in managing travel patterns to maximize opportunities for tourist comfort, making Curug Cilember a mainstay destination that must be visited.